"NAVIGATING THE NEW EDUCATIONAL FRONTIER: UNDERSTANDING THE IMPACT OF AI TECHNOLOGIES AMONG PRE-UNIVERSITY STUDENTS" - Pratiba Narayanasamy; Wan Suriatty Mazlan; Mustafa Kamal Ariffin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
In this era of drastic technological advancements, most of the students and teachers are experiencing the usage of artificial intelligence technologies in classrooms. Artificial intelligence (AI), sometimes called machine intelligence or virtual artificial agent are intelligence demonstrated by machines. These technologies that are used, sometimes are in contrast to the natural intelligence displayed by humans. In University, it is helping the students in getting additional tutoring support when they could not attend a class due to medical or any other personal reasons. These are also technologies that helps students by giving appropriate feedback with regards to their performance before submitting their assessments or group work task. Some varsities are even using AI technologies even to the extent of having human robots in handling most of the sessions in a regular classroom. This study seeks to understand the usage and impact of Artificial Intelligence technologies from a student's perspective in their learning progress at Pre-University level.